Interactions between Fusarium verticillioides, Aspergillus flavus and insects in improved maize populations in lowland Africa - Cardwell, K.; Kling, J.; Maziya-Dixon, B.B.; Bosque Pérez, N.A. (Scientific Societies, 2000)
An experiment was designed to compare cycles of selection of four maize genotypes for ear- and grain-quality characteristics, interactions with Aspergillus flavus and Fusarium verticillioides infection, and insect ear infestation in two seasons. Mean infection levels by A. flavus and F. verticillioides were significantly higher in inoculated rows than in the controls. The F. verticillioides-inoculated rows had significantly more coleopteran beetles and lepidopteran borers per ear than the controls and A. flavus-inoculated rows. Genotypes and cycles of selection within genotype were not different with respect to number of insects or percent fungal incidence in the ear, but they were different for husk extension, field weight, 100-grain weight, and grain density. Inoculation with either fungus resulted in significantly higher percentage of floaters (i.e., loss of grain density) and lower grain weight than the controls. Aflatoxin (B1 and B2) in A. flavus-inoculated rows averaged 327 ppb in the first season and 589 ppb in the second (dryer) season. Fumonisin levels in F. verticillioides-inoculated rows did not differ between seasons, with an average of 6.2 ppm across seasons. In the noninoculated control rows, fumonisin was significantly higher in the first (5.3 ppm) than in the second (3.1 ppm) season. For all genotypes, husk extension and yield parameters decreased in the fungal-inoculated treatments. General ear-rot scoring was significantly correlated with incidence of F. verticillioides in kernels and grain-weight loss but not with A. flavus in the grain.